Acculturation of islamic culture as a symbol of siraman rituals in java traditional wedding - Suyadi Suyadi; Ahmad Fikri Sabiq (IAIN Salatiga, 2020)
The purpose of this study was to determine the acculturation of Islam and local culture in the Javanese traditional wedding ceremony. This research uses a qualitative approach. Collecting data by interview, observation, and documentation. The location of this research is in Kedungjati, Grobogan. Data analysis using the semiotic theory of Roland Barthes. The result of this research is that the ritual of siraman in Javanese traditional wedding in Kedungjati has connotation, denotation, and myth meaning as in the semiotic analysis of Roland Barthes. The siraman ritual has sixteen stages of the process, namely the installation of bleketepe, sungkeman, ngracik toyo, praying, siraman, sesuci, pecah kendhi pratolo, pondhongan or gendongan, ganti busana, pangkas rikma, tanam rikma, pagas tumpeng, Dulang pungkasan, adol dawet, itung duwit, and simpen pedaringan.